Análise estatística da influencia dos parâmetros de corte na rugosidade no torneamento do aço microligado DIN 38MnSiVS5 - Nunes, Luciano Tadeu (2011)
The condition of a machined surface is the result of a process that involves plastic deformation, rupture, elastic recovery, heat generation, vibration, residual stress and, sometimes, chemical reactions. All these factors can provide different effects on the new surface generated. The term surface integrity can embrace a great number of changes in the surface. For a conventional machining process, surface integrity can be classified in surface changes and changes in sub-surface. In this work the effect of the main cutting parameters, cutting speed (vc), feed rate (f), tool nose radius (rε) and cutting fluid on surface roughness parameters (Ra, Ry, Rq Rku, Rsk) and profile of a machined surface are analysed. The vibration signal was also obtained during the operation in order to find correlation to the roughness parameters. For more reliability of the results it was used a statistical analysis. The results shown that the feed rate and tool nose radius were the major cutting parameters affecting surface roughness (parameter Rq) and it was found a good correlation between Rq parameter and vibration signal.